2011
DOI: 10.1001/archdermatol.2010.284
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Facial Milia in Patients With Loeys-Dietz Syndrome

Abstract: Background: Loeys-Dietz syndrome (LDS) results from mutations in the TGFBR1 or TGFBR2 genes and is known to cause aggressive cardiovascular disease, including aortic aneurysms and dissections at an early age. Currently, craniofacial, skeletal, and cardiovascular findings play an important role in early recognition of the disease. While many patients do have recognizable cutaneous features of LDS, little information about associated skin findings has been reported. Observations: Four unrelated patients with LDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Hernias were of different types (diaphragmatic, inguinal, or umbilical) and together with joint laxity were registered in half of patients. Cutaneous findings appeared extremely frequent including translucent skin, easy bruising and striae; together with facial milia, described in half mutated patients, skin features appeared as extremely useful handle for diagnosis [14]. Overall, our data confirm broad overlap between LDS phenotypes caused by TGFBR1/2 pathogenic variants, as previously assessed [6].…”
Section: Discussionsupporting
confidence: 83%
“…Hernias were of different types (diaphragmatic, inguinal, or umbilical) and together with joint laxity were registered in half of patients. Cutaneous findings appeared extremely frequent including translucent skin, easy bruising and striae; together with facial milia, described in half mutated patients, skin features appeared as extremely useful handle for diagnosis [14]. Overall, our data confirm broad overlap between LDS phenotypes caused by TGFBR1/2 pathogenic variants, as previously assessed [6].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, our proband presented with prenatally detected skeletal abnormalities; including club feet and hand abnormalities. He also demonstrated multiple facial milia and respiratory distress that have been reported as early signs of LDS [Lloyd et al, ; Kuppler et al, ]. While the club foot/feet and hand contractures were previously described in 23% and 13% of a group of 65 LDS patients, respectively [Erkula et al, ], the syndactyly and absent distal phalanges has not been previously reported in conjunction with LDS.…”
Section: Discussionmentioning
confidence: 93%
“…2 The second, 24-year-old patient, was included in a study of 25 patients with LDS. 3 She had multiple facial milia around the eyes and malar AV. A mutation in TGFBR2 was identified.…”
Section: Patientmentioning
confidence: 99%
“…Of additional interest, 3 other patients in that same study also had facial milia and a TGFBR2 mutation. 3 Therefore, milia may be a feature of TGFBR2-related LDS.…”
Section: Patientmentioning
confidence: 99%
See 1 more Smart Citation